Stalking Perpetration in Hong Kong: Exploring the Stalker-Victim Relationship - Chan, Heng Choon (Oliver) (Victims & offenders, 2022)
Little is known about stalking perpetration in the Asian context. This study examines the dynamics of stalking perpetration (i.e., offending characteristics, perpetration behaviors, motives, and other violent and nonviolent behaviors) among adults in Hong Kong by stalker-victim relationship (i.e., ex-intimate partner, non-intimate non-stranger, and stranger). Using a large sample of university students (N = 2,496) aged 18–40, the lifetime prevalence rate of stalking perpetration was 1.8% (n = 45; 3% males [n = 33], 0.9% females [n = 12]). Relative to non-stranger stalkers, significantly more stranger stalkers self-reported that they had stalked in the preceding month, and reported shorter stalking durations. A number of significant differences were found between different stalker-victim relational groups (i.e., ex-intimate partner vs. non-intimate non-stranger, and non-stranger vs. stranger) in stalking perpetration behaviors and motives. Relative to those who stalked a non-intimate non-stranger, significantly more ex-intimate stalkers reported that they had attacked/attempted to attack their victim’s pet. Conversely, stranger stalkers were more likely than non-stranger stalkers to have attacked/attempted to attack their victim or a friend or coworker of the victim. The findings may offer some Hong Kong-specific insights for police and threat assessment professionals when formulating investigation and management plans.